Reconstructing Educational and Professional Pathways After Postgraduate Graduation - Brenda Colin; Guadalupe Barajas (Revista Electrónica de Investigación Educativa)
This article presents the results of research into the educational and professional pathways of graduates of the master’s degree in educational innovation at the University of Sonora (UNISON), Mexico. A phenomenological qualitative descriptive approach was employed with narrative inquiry. In all, 40 narratives were obtained from eight graduating classes, which reflected two types of pathway: an educational and pedagogical pathway and a pathway of obstinate learning. It was also found that these pathways are consecutive under subjective, objective, social, cultural, or economic structures.